2020
DOI: 10.3389/fphys.2020.00311
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Reverses the Alterations in Gut Microbiota Upon Cold Exposure and Promotes Cold-Induced Weight Loss

Abstract: We are extremely grateful to students at the Guangzhou Sport University for experimental assistance, sample collection, and discussions. We gratefully acknowledge all the study staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…Six animal studies reported energy intake (37,38,43,45,49,51) and two studies reported energy expenditure (38,43), respectively. Besides, 18 (23,35‐45,47,49‐53) of the 21 animal studies were randomized studies, whereas the other 3 were longitudinal intervention and nonrandom control studies (24,46,48).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six animal studies reported energy intake (37,38,43,45,49,51) and two studies reported energy expenditure (38,43), respectively. Besides, 18 (23,35‐45,47,49‐53) of the 21 animal studies were randomized studies, whereas the other 3 were longitudinal intervention and nonrandom control studies (24,46,48).…”
Section: Resultsmentioning
confidence: 99%
“…In animal studies, long‐term training ranging from 4 to 16 weeks served as an exercise intervention (Table 2). Treadmill running (in endurance training, resistance training, or high‐intensity interval training protocols) (24,36,39‐41,44‐46,48‐51,53), voluntary wheel running (23,35,37,42,43), and swimming (47,52) were the major forms of exercise intervention in these studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In turn, exercise can promote the proliferation of specific bacterial strains, including those of Veillonella [ 109 ]. A combination of physical activity with cold exposure occurred to promote more extensive changes in the gut microbiome and subsequently increased WAT browning ant weight loss more effectively than exercise or cold exposure alone [ 110 ]. In turn, mice challenged with caloric restriction or intermittent fasting (both associated with excessive WAT browning) have also been reported to have alternations in intestinal microbiota.…”
Section: Non-pharmacological Interventions Aiming At White Adiposementioning
confidence: 99%